Patient’s knowledge and perception of anaesthesia and anaesthesiologist: data from a tertiary centre in Pakistan - Siddiqui, Khalid Maudood; Islam, Fahad; Salim, Bushra; Asghar , Muhammad Ali (Journal of the Pakistan Medical Association, 2026)
Objective: To assess patients’ knowledge of anaesthesia and the role of anaesthesiologists. Method: The cross-sectional study was conducted at the Aga Khan University Hospital, Karachi from October 2020 to April 2021 and comprised patients of either gender aged 18-60 years who were undergoing preoperative assessment. Data was collected through a structured questionnaire evaluating knowledge about anaesthesia and anaesthesiologists, focusing on perioperative roles and responsibilities. Data was analysed using RStudio version 4.1.2. Results: Of the 150 patients with mean age 49.14±8.49 years, 82 (54.7%) were females and 70 (45.3%) were males. Overall, 100(66.7%) patients had good and 50(33.3%) had poor knowledge. Those with prior anaesthesia experience had significantly better knowledge (p<0.001). Individuals aged up to 40 years exhibited poorer knowledge compared to older participants (p=0.033). Higher knowledge levels were observed among those who recognised anaesthesiologists as specialists (p=0.016) and understood the importance of preoperative assessments (p<0.001). Awareness about the anaesthesiologists’ role during continuous monitoring and postoperative care was also significantly associated with better knowledge (p<0.001). Conclusion: A substantial lack of patient awareness about anaesthesia and the role of anaesthesiologists was found. Key Words: Anaesthesia knowledge, Anaesthesiologist awareness, Patient education, Perioperative care, Preoperative assessment.